Vitamin B12 deficiency and cognitive impairment: A comprehensive review of neurological impact - Milind Umekar; Tanvi Premchandani; Amol Tatode; Mohammad Qutub; Neha Raut; Jayshree Taksande; Ujban Md. Hussain (Brain Disorders)
Cognitive impairment, a prevalent issue in aging populations, significantly affects quality of life and public health systems. Among various contributing factors, Vitamin B12 deficiency emerges as a critical yet modifiable risk factor, impacting neurological and cognitive health. Vitamin B12, an essential micronutrient derived from animal-based foods, is vital for myelin integrity, neurotransmitter synthesis, and homocysteine metabolism. Its deficiency disrupts these processes, leading to neurotoxic effects such as oxidative stress, vascular damage, and neurodegeneration, which exacerbate cognitive decline. This review combines evidence from human and animal studies on the neurocognitive impacts of Vitamin B12 deficiency and evaluates supplementation strategies. It underscores the multifactorial nature of B12 deficiency, driven by dietary inadequacies, physiological changes, and environmental factors, especially in high-risk groups such as the elderly and vegetarians. Proactive measures, including routine screening, dietary adjustments, and early supplementation, are essential to prevent deficiency-related cognitive impairments. Advancements in biomarkers and neuroimaging also promise improved diagnosis and intervention strategies, highlighting an interdisciplinary approach to optimizing cognitive health outcomes.